Impact of Compensation Work Culture, And Commitment of The Organization To The Employer's Works In Agrodana Futures Surabaya - Dedik Anugerah; Endang Muryani; Dwi Widi Hariyanto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
Companies must have high-quality human resources along with scientific and technological advances. Human resources play an important role in today's various industries. To deal with the factors of employment in such a way takes a lot of effort. The main purpose of this article is to find out how the performance of employees at PT. Agrodana Futures Surabaya is influenced by salary, working environment, and organizational commitment. A quantitative approach is used in this kind of research. Primary (survey) data and secondary (related library study) data are the types of data and sources used in this research. The participants in this study are all employees of PT. Agrodana Futures Surabaya. Using probability sampling, samples were taken for this study, with a total of 75 respondents. This research uses questionnaire techniques, documentation, observation, and library expression to gather data. The validity test of the information in the expression emphasized the legitimacy test, the dependence test, and the speculation test. Based on the results of data analysis, the performance of employees at PT. Agrodana Futures Surabaya is influenced by the cost factor (thitung 7,638 > table 1,9939), the work culture (Thitung 2,839 > table 1,99939), and the commitment of the organization (5,213) > table 1.9939. To further develop employee performance, PT. Agrodana Futures Surabaya is advised to encourage its employees to think creatively and dare to take risks in order to increase employee confidence in accepting the values and goals of the company.